A Case Report On Intraocular Cystocercosis and the Occurrence of A Live Free Floating Cyst in the Anterior Chamber of the Eye - Musa, Juna; Rakovica, Loran; Hallunovaj, Luela; Horjeti, Edlira; Kola, Erisa; Guy, Ali; Simaku, Ermal; Abdullahu, Blina; Hyseni, Fiolla; Tandili, Alketa (Archives of Clinical and Medical Case Reports, 2020)
Ocular cysticercosis is a parasitic infestation caused by Cysticercus cellulosae, known as the larval form of Taenia solium. It occurs through consumption of fecally contaminated food or by intestinal autoinfection. Ocular cysticercosis can involve the ocular adnexa, the subconjunctival space, and the anterior and posterior segments of the eye. Anterior chamber cysticercosis is unusual. It has a worldwide distribution, most commonly found in developing countries with poor sanitation like East Asia, sub-Saharan Africa and some parts of Latin America. Due to its varied presentation, cysticercosis may pose a diagnostic challenge to health professionals. Early diagnosis and management can prevent vision loss and optimize visual outcomes. Below we report a rare case of an 11-year-old female presenting with blurriness and conjunctival injection to her left eye after visiting the countryside. Initial BCVA was noted to be 0.4. Histopathological findings showed scolex in the left anterior chamber and membranous cyst wall suggestive of cysticercus cellulosae. Management with viscoexpression, fixation of cyst along with topical and systemic medication showed satisfactory improvement with a post-operative BCVA of 1.0. <gdiv></gdiv>